Growth Performance of Eucalyptus tereticornis and E. Camaldulensis Progenies under Various Levels of Soil Salinity - Singh, Avtar; Toky, O. P.; Dhillon, G. P. S. (Indian Forester, 2010)
The study was conducted by transplanting one and half month old seedlings of six progenies, three each of Eucalyptus tereticornis and E. camaldulensis, in the pots filled with eight levels of artificially created soil salinity levels (ECe) i.e. control, 2, 4, 6, 8, 10, 12, and 14 dSm-1. The experiment was conducted by following completely randomized design with three replications. The data on plant height, collar diameter and number of leaves per plant were recorded after 90 days of study. All the growth parameters of both the species recorded significant differences among salinity treatments. The maximum values were recorded in control and the lowest values were found at salinity level of ECe 14 dSm-1 . Significant genetic variation was noticed in both the species for all the growth parameters. E. camaldulensis recorded significantly higher growth traits than respective values of E. tereticornis.